Should Event Organizers Prevent Resale of Tickets? - Cui, Yao; Duenyas, Izak; Şahin, Özge (Management Science, 2014)
We are interested in whether preventing resale of tickets benefits the capacity providers for sporting and entertainment events. Common wisdom suggests that ticket resale is harmful to event organizers' revenues, and event organizers have tried to prevent resale of tickets. For instance, Ticketmaster recently proposed paperless (nontransferrable) ticketing, which would severely limit the opportunity to resell tickets. We consider a model that allows resale from both consumers and speculators with different transaction costs for each party. Surprisingly, we find that this wisdom is incorrect when event organizers use fixed pricing policies; in fact, event organizers benefit from reductions in consumers' (and speculators') transaction costs of resale. Even when multiperiod pricing policies are used, we find that an event organizer may still benefit from ticket resale if his capacity is small. Although paperless ticketing is suggested as a way to reduce ticket resale and prevent speculators from buying tickets, our results suggest that it may reduce the capacity providers' revenues in many situations. Instead, we propose ticket options as a novel ticket pricing mechanism. We show that ticket options (where consumers would initially buy an option to buy a ticket and then exercise at a later date) naturally reduce ticket resale significantly and result in significant increases in event organizers' revenues. Furthermore, since a consumer only risks the option price (and not the whole ticket price) if she cannot attend the event, options may face less consumer resistance than paperless tickets. This paper was accepted by Serguei Netessine, operations management.